2017
DOI: 10.1016/j.ppnp.2017.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Flavor physics and CP violation

Abstract: We currently live in the age of the CKM paradigm. The 3 × 3 matrix that links (d, s, b) quarks to (u, c, t) in the charged current weak interaction, being complex and nominally with 18 parameters, can be accounted for by just 3 rotation angles and one CP violating (CPV) phase, with unitarity and the CKM phases triumphantly tested at the B factories. But the CKM picture is unsatisfactory and has too many parameters. The main aim of Flavor Physics and CP violation (FPCP) studies is the pursuit to uncover New … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 361 publications
0
15
0
Order By: Relevance
“…We had pointed out earlier [47] that g2HDM could in principle make the ratio B(B → µν)/B(B → τν) deviate from the SM expectation of 0.0045, where 2HDM II shares the same value [45]. But it was only by checking explicitly [46] that we found that, indeed, B → τν would be SM-like, but B → µν could be more easily shifted, even when one respects Eq.…”
Section: Glimpse Of the Coming New Flavor Eramentioning
confidence: 61%
“…We had pointed out earlier [47] that g2HDM could in principle make the ratio B(B → µν)/B(B → τν) deviate from the SM expectation of 0.0045, where 2HDM II shares the same value [45]. But it was only by checking explicitly [46] that we found that, indeed, B → τν would be SM-like, but B → µν could be more easily shifted, even when one respects Eq.…”
Section: Glimpse Of the Coming New Flavor Eramentioning
confidence: 61%
“…which is relatively precise (subject to mild QED corrections) since it involves only lepton masses. The prediction for 2HDM type II is the same [1,4,5]. The B → ν ( = μ, τ ) decay rates can deviate from SM predictions in the presence of the SLQ S 1 .…”
Section: Formalismmentioning
confidence: 82%
“…The B → μν decay is further helicity suppressed, and has not been observed so far. It was pointed out recently that, while the ratio B(B → μν)/B(B → τν) is predicted to be the same for both SM and the popular 2HDM type II [1], the value could deviate [4,5] from the SM expectation in the more general 2HDM (g2HDM) that allows extra Yukawa couplings.…”
Section: Introductionmentioning
confidence: 99%
“…Many good reviews exist addressing CP violation in hadrons (see, for example, [35][36][37][38][39]). This work is dedicated exclusively to discussing direct CP violation in b-and c-hadron systems.…”
Section: Introductionmentioning
confidence: 99%